Method for producing ferrite calcined body and sintered ferrite magnet
Patent Information
- Application Number
- JP2022026267
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-26
- Filing Date
- 2022-02-23
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-02-23
AI Technical Summary
【0031】 本開示によれば、高い磁石特性を有するフェライト焼結磁石を得ることが可能なフェライト仮焼体および当該フェライト仮焼体を用いたフェライト焼結磁石の製造方法を提供することができる。
Smart Images

Figure 0007639733000001 
Figure 0007639733000002 
Figure 0007639733000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a calcined ferrite body and a sintered ferrite magnet. [Background technology]
[0002] Although the maximum energy product of ferrite sintered magnets is only one-tenth that of rare-earth sintered magnets (e.g., NdFeB sintered magnets), they offer excellent cost performance because their main raw material is inexpensive iron oxide, and they are characterized by being extremely chemically stable.As a result, they are used for a variety of purposes, including various motors and speakers, and are still the largest magnet material in terms of global production volume.
[0003] Among the various applications in which sintered ferrite magnets are used, such as motors and speakers, there is a strong demand for high performance materials in motors for automotive electrical equipment, motors for home appliances, etc. In recent years, against the backdrop of rising prices of rare earth raw materials and the emergence of procurement risks, the application of sintered ferrite magnets to industrial motors and drive motors and generators for electric vehicles (EV, HV, PHV, etc.), where only rare earth sintered magnets were used until now, is being considered.
[0004] A typical sintered ferrite magnet is a Sr ferrite with a magnetoplumbite structure, and its basic composition is SrFe 12 O 19 In the late 1990s, SrFe 12 O 19 Sr 2+ Part of La 3+ Replaced with Fe 3+ Part of Co 2+ The magnetic properties of ferrite magnets have been greatly improved with the commercialization of Sr-La-Co sintered ferrite magnets (hereafter sometimes abbreviated as "SrLaCo magnets") in which the Cr was replaced with Sr. In 2007, Ca-La-Co sintered ferrite magnets (hereafter sometimes abbreviated as "CaLaCo magnets"), which have even better magnetic properties, were developed and are currently in practical use.
[0005] By the way, sintered ferrite magnets are manufactured through the following steps: mixing of raw materials, calcination, crushing, molding, sintering, and processing. In general, "calcination" refers to the process of heating the mixed raw materials to form a ferrite phase (sometimes called a ferrite compound or M phase) with a hexagonal magnetoplumbite (M-type) structure through a solid-state reaction, and the product obtained by calcination is called the "calcined body."
[0006] Conventionally, it has been common practice to increase the constituent phase ratio of the ferrite phase (hereinafter sometimes referred to as "phase ratio") at the stage of the calcined body (preferably to 100 mass % = M phase single phase). This is because the phase ratio of the M phase is also high in the ferrite sintered magnet obtained by crushing, molding and sintering the calcined body, and high magnetic properties can be expected. In other words, hematite phase (α-Fe2O3), orthoferrite phase (LaFeO3, etc.), and spinel ferrite phase (CoFe2O4, etc.), other than the ferrite phase (M phase), are heterophases, and it has been thought that these heterophases should not be included in the calcined body. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2020-155609 A
[0008] Patent Document 1 describes a method for producing a Ca-La-Co based sintered ferrite magnet in which part of the Co is replaced with Zn, using a calcined powder containing 12 to 30 mass% hematite phase, 3 to 10 mass% La orthoferrite phase, and 5 to 10 mass% spinel ferrite phase.
[0009] In essence, the invention described in Patent Document 1 relates to a CaLaCo magnet with a unique composition in which the La content exceeds 0.55 in atomic ratio and part of the Co is substituted with Zn. By using a calcined body that has been calcined at a low temperature and in which the solid-phase reaction has not yet completed (the solid-phase reaction is in progress), adding trace amounts of SiO2 and CaO, molding and sintering the body, it is possible to obtain magnetic properties equivalent to those obtained by using a calcined body of the same composition that has been calcined at a high temperature and in which the solid-phase reaction has completed (see, for example, paragraph 0029 of Patent Document 1).
[0010] However, the invention described in Patent Document 1 has a unique composition in which the La content exceeds 0.55 in atomic ratio and part of the Co is replaced by Zn, resulting in a high residual magnetic flux density (hereinafter referred to as "B r Although the coercive force (hereafter referred to as "H cJ ") is low, and the magnetic properties are not sufficient for use in the aforementioned industrial motors, drive motors and generators for electric vehicles, and the like. Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present disclosure is to provide a ferrite calcined body that can produce a sintered ferrite magnet having excellent magnetic properties, and a method for producing a sintered ferrite magnet using the ferrite calcined body.
[0012] The present inventors have conducted extensive research into further improving the performance of CaLaCo magnets. As a result, they have discovered that, contrary to the conventional idea that a calcined body must be a single M phase, if a specific amount of spinel ferrite phase is contained in a calcined body in which solid-phase reaction has been completely completed, the magnetic properties of a sintered magnet produced using the calcined body are improved. Furthermore, they have discovered that the specific amount of spinel ferrite phase contains more Mn, which is inevitably contained as an impurity and tends to deteriorate the magnetic properties, than the ferrite phase (M phase). In other words, they have discovered that the spinel ferrite phase has the function of taking in and rendering harmless Mn and improving the magnetic properties, and is no longer a different phase but an essential constituent phase in the calcined body. [Means for solving the problem]
[0013] That is, the ferrite calcined body of the present disclosure is a ferrite calcined body having a hexagonal M-type magnetoplumbite structure containing the metal elements Ca, R, A, Fe and Co (R is at least one rare earth element essentially containing La, and A is Sr and / or Ba), and a spinel ferrite phase containing Co, and is characterized in that it contains 70 mass% or more and less than 100 mass% of the ferrite phase and more than 0 mass% and 30 mass% or less of the spinel ferrite phase.
[0014] The ferrite calcined body of the present disclosure may further contain more than 0 mass % and less than 3 mass % of La orthoferrite phase.
[0015] It is preferable that the ferrite calcined body of the present disclosure does not substantially contain a hematite phase.
[0016] The calcined ferrite body of the present disclosure preferably contains the spinel ferrite phase in an amount of 5% by mass or more and 30% by mass or less.
[0017] The calcined ferrite body of the present disclosure preferably contains the spinel ferrite phase in an amount of 5% by mass or more and 25% by mass or less.
[0018] The calcined ferrite body of the present disclosure preferably contains the spinel ferrite phase in an amount of 10% by mass or more and 20% by mass or less.
[0019] In the ferrite calcined body of the present disclosure, the calcined body contains Mn, and it is preferable that the Mn content in the spinel ferrite phase is greater than the Mn content in the ferrite phase.
[0020] In the ferrite calcined body of the present disclosure, Mn is preferably contained only in the spinel ferrite phase.
[0021] In the ferrite calcined body of the present disclosure, the spinel ferrite phase contains Ca, Fe, Co and Mn, and when the total amount of the elements is 100 at%, Ca: more than 0at% and less than 10at%, Fe: 80at% or more and 90at% or less, Co: 2 at% or more and 15 at% or less, and Mn: more than 0at% and less than 5at%, It is preferable that the composition ratio is as follows:
[0022] In the ferrite calcined body of the present disclosure, when the total amount of Ca, R, A, Fe and Co in the ferrite phase is 100 at%, Ca: 2.0at% or more and 6.5at% or less, R: 2.0at% or more and 6.5at% or less, A: 0at% or more and 2at% or less, Fe: 83 at% or more and 92 at% or less, and Co: 1.5at% or more and 6.5% or less, It is preferable that the composition ratio is as follows:
[0023] The method for producing a ferrite sintered magnet according to the present disclosure includes a molding step of molding a powder of the ferrite calcined body according to the present disclosure to obtain a molded body, and a sintering step of sintering the molded body to obtain a sintered body.
[0024] In the method for producing a sintered ferrite magnet according to the present disclosure, the calcined body is preferably calcined at a temperature of 1250°C or higher and 1350°C or lower.
[0025] In the method for producing a sintered ferrite magnet according to the present disclosure, the calcined body is preferably calcined at a temperature of 1280°C or higher and 1330°C or lower.
[0026] In the method for producing a sintered ferrite magnet according to the present disclosure, the calcined body is preferably calcined at a temperature of 1290°C or higher and 1320°C or lower.
[0027] In the method for producing a sintered ferrite magnet according to the present disclosure, the calcined body is preferably calcined in a rotary kiln.
[0028] The method for producing a sintered ferrite magnet according to the present disclosure preferably further includes, after the calcined body preparation step and before the compacting step, a step of adding more than 0 mass % and not more than 1.5 mass % of SiO2 relative to 100 mass % of the calcined body.
[0029] In the method for producing a sintered ferrite magnet according to the present disclosure, it is preferable to further include a step of adding, after the calcined body preparation step and before the molding step, more than 0 mass % and not more than 1.5 mass % CaCO3, calculated as CaO, relative to 100 mass % of the calcined body.
[0030] The method for producing a sintered ferrite magnet according to the present disclosure preferably further comprises, after the calcined body preparing step and before the compacting step, a step of adding 2 mass % or less of Cr2O3 relative to 100 mass % of the calcined body. Effect of the Invention
[0031] According to the present disclosure, it is possible to provide a ferrite calcined body that can produce a sintered ferrite magnet having excellent magnetic properties, and a method for producing a sintered ferrite magnet using the ferrite calcined body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] 1. Ferrite calcined body The ferrite calcined body of the present disclosure is The magnetron has a ferrite phase having a hexagonal M-type magnetoplumbite structure containing the metal elements Ca, R, A, Fe, and Co (R is at least one rare earth element essentially containing La, and A is Sr and / or Ba), and a spinel ferrite phase containing Co, and contains 70 mass% or more and less than 100 mass% of the ferrite phase and more than 0 mass% and 30 mass% or less of the spinel ferrite phase.
[0033] The ferrite calcined body of the present disclosure further contains more than 0 mass % and less than 3 mass % of an orthoferrite phase, and is substantially free of a hematite phase.
[0034] The main phase constituting the ferrite calcined body is a ferrite phase having a hexagonal magnetoplumbite (M-type) structure. In general, magnetic materials, particularly sintered magnets, are defined as being composed of multiple compounds.
[0035] "Having a hexagonal magnetoplumbite (M-type) structure" means that in an X-ray diffraction measurement of a ferrite calcined powder under typical conditions, an X-ray diffraction pattern of a hexagonal magnetoplumbite (M-type) structure is mainly observed.
[0036] The ferrite phase contained in the ferrite calcined body is 70 mass % or more and less than 100 mass %. If it is less than 70 mass %, a high B r and H cj If the content is 100 mass %, it is not possible to obtain high magnetic properties.
[0037] (A m Fe 3-m The spinel ferrite phase having a composition of 0 (A is Co, Mn, Ni, Cu, Zn, Ca, etc.) is a phase having a spinel structure of an equiaxed crystal system. The ratio of the spinel ferrite phase contained in the ferrite calcined body is more than 0 mass% and 30 mass% or less. When it is 0 mass%, high H cj If the content is more than 30 mass%, a high B rand H cj The content is preferably from 5% by mass to 30% by mass, more preferably from 5% by mass to 25% by mass, and further preferably from 10% by mass to 20% by mass.
[0038] The orthoferrite phase (such as LaFeO3) has a perovskite structure and is a different phase in the ferrite calcined body of the present disclosure, but if it is contained in an amount of more than 0 mass% and less than 3 mass%, it has almost no effect on the magnetic properties. If it is contained in an amount of 3 mass% or more, the proportion of different phases increases (the proportion of ferrite phase decreases), making it impossible to obtain high magnetic properties.
[0039] The hematite phase (α-Fe2O3) is a different phase in the ferrite calcined body of the present disclosure. The ferrite calcined body of the present disclosure does not substantially contain a hematite phase. "Substantially does not contain" means that the hematite phase cannot be confirmed by X-ray diffraction. If the hematite phase is contained in the ferrite calcined body, it will cause a significant decrease in magnetic properties (especially saturation magnetization).
[0040] The metal elements contained in each phase can be measured, for example, by EDS (energy dispersive X-ray spectroscopy) analysis using a FE-SEM (field emission scanning electron microscope). The ferrite phase of the present disclosure contains Ca, R, A, Fe, and Co, and when the total amount of each element (the total amount of each element of Ca, R, A, Fe, and Co) is taken as 100 at%, Ca: 2.0at% or more and 6.5at% or less, R: 2.0at% or more and 6.5at% or less, A: 0at% or more and 2at% or less, Fe: 83 at% or more and 92 at% or less, and Co: 1.5at% or more and 6.5% or less, This is the composition ratio.
[0041] The Ca content is preferably 2.0 at % or more and 6.5 at % or less. If the Ca content is less than 2.0 at % or exceeds 6.5 at %, high magnetic properties cannot be obtained.
[0042] The content of R is preferably 2.0 at% or more and 6.5 at% or less. If it is less than 2.0 at% or exceeds 6.5 at%, high magnetic properties cannot be obtained. R is at least one rare earth element, and is an element that essentially contains La. The content of rare earth elements other than La is preferably 50% or less of the total amount of R in atomic ratio.
[0043] The content of the A element is preferably 0 at% or more and 2 at% or less. The A element is Sr and / or Ba. The effect of the present invention is not impaired even if the A element is not contained, but by adding the A element, the crystals in the calcined body are made finer and the aspect ratio is reduced, so that the effect of further improving the magnetic properties can be obtained. If the A element exceeds 2 at%, high magnetic properties cannot be obtained.
[0044] The Fe content is preferably 83 at % or more and 92 at % or less. If the Fe content is less than 83 at % or exceeds 92 at %, high magnetic properties cannot be obtained.
[0045] The Co content is preferably 1.5 at % or more and 6.5 at % or less. If the Co content is less than 1.5 at % or exceeds 6.5 at %, high magnetic properties cannot be obtained.
[0046] In addition, the spinel ferrite phase contains Ca, Fe, Co, and Mn, and when the total amount of each element (the total amount of each element of Ca, Fe, Co, and Mn) is 100 at%, Ca: more than 0at% and less than 10at%, Fe: 80at% or more and 90at% or less, Co: 2 at% or more and 15 at% or less, and Mn: more than 0at% and less than 5at%, This is the composition ratio.
[0047] The Ca content is preferably more than 0 at % and not more than 5 at %. If the Ca content is less than 2.0 at % or exceeds 6.5 at %, high magnetic properties cannot be obtained.
[0048] The content of Fe element is preferably 80 at % or more and 90 at % or less. If it is less than 80 at % or exceeds 90 at %, high magnetic properties cannot be obtained.
[0049] The content of Co element is preferably 2 at % or more and 15 at % or less.If it is less than 1.5 at % or exceeds 6.5 at %, high magnetic properties cannot be obtained.
[0050] The Mn element content is preferably more than 0 at % and not more than 5 at %. If it exceeds 0 at % or 5 at %, high magnetic properties cannot be obtained.
[0051] Mn is contained as an inevitable impurity in the Fe compound, which is the raw material powder. When Mn is contained in the ferrite phase, it causes a decrease in magnetic properties, but high magnetic properties can be obtained by making the Mn content in the spinel ferrite phase higher than the Mn content in the ferrite phase. More preferably, Mn is not contained in the ferrite phase, and is contained only in the spinel ferrite phase. Note that Mn is not limited to being contained as an inevitable impurity, and may also be added intentionally.
[0052] In addition, the atomic ratio of metal elements in the entire ferrite calcined body of the present disclosure, including the ferrite phase and the spinel ferrite phase, can be expressed by the following general formula. The general formula showing the atomic ratio of the metal elements Ca, R, A, Fe and Co (R is at least one rare earth element and essentially contains La, and A is Sr and / or Ba): Ca 1-x―y R x A y Fe 2n-z Co z In the formula, x, y, z, and n (2n is a molar ratio expressed as 2n=(Fe+Co) / (Ca+R+A)) are 0.3≦1−x―y≦0.65, 0.3≦x≦0.65, 0≦y≦0.2, 0.25≦z≦0.65, and 4.5≦n≦7 is satisfied, Contains more than 0 mass% and not more than 0.5 mass% Mn, calculated as MnO.
[0053] The above general formula is expressed by the atomic ratio of metal elements, but the composition containing oxygen (O) is expressed by the general formula: Ca 1-x―y R x A y Fe 2n-z Co z O α The number of moles of oxygen α is basically α=19, but it varies depending on the valences of Fe and Co, and the values of x, y, z, and n. In addition, the ratio of oxygen to metal elements changes due to oxygen vacancies when fired in a reducing atmosphere, changes in the valence of Fe in the ferrite phase, changes in the valence of Co, and the like. Therefore, the actual atomic ratio α of oxygen may deviate from 19. Therefore, in this disclosure, the composition is expressed in terms of the atomic ratio of metal elements whose composition is easiest to identify.
[0054] An example of a method for producing a sintered ferrite magnet according to the present disclosure, including the method for producing the calcined ferrite powder according to the present disclosure described above, will be described below.
[0055] 2. Manufacturing method of sintered ferrite magnets The raw powder may be a compound such as oxide, carbonate, hydroxide, nitrate, or chloride of each metal, regardless of its valence. The raw powder may be dissolved in a solution. Examples of Ca compounds include carbonate, oxide, or chloride of Ca. Examples of R compounds include rare earth oxides such as La2O3, rare earth hydroxides such as La(OH)3, and rare earth carbonates such as La2(CO3)3·8H2O. Examples of A element compounds include carbonate, oxide, or chloride of Sr and / or Ba. Examples of Fe compounds include iron oxide, iron hydroxide, iron chloride, mill scale, and the like. Examples of Co compounds include oxides such as CoO and Co3O4, hydroxides such as CoOOH and Co(OH)2, carbonates such as CoCO3, and basic carbonates such as m2CoCo3·m3Co(OH)2·m4H2O (m2, m3, and m4 are positive numbers). Mn is contained in Fe compounds as an inevitable impurity or as an additive.
[0056] In order to promote the reaction during calcination, compounds containing B (boron), such as B2O3 and H3BO3, may be added up to about 1 mass % as necessary. The addition of H3BO3 is particularly effective in improving the magnetic properties. The amount of H3BO3 added is preferably 0.3 mass % or less, and most preferably about 0.1 mass %. H3BO3 also has the effect of controlling the shape and size of crystal grains during sintering, so it may be added after calcination (before pulverization or sintering) or both before and after calcination.
[0057] Raw material powders satisfying the components and composition of the ferrite calcined body of the present disclosure are mixed to obtain a mixed raw material powder. The blending and mixing of the raw material powders may be performed in either a wet or dry manner. The raw material powders can be mixed more uniformly by stirring with a medium such as steel balls. In the case of the wet method, it is preferable to use water as a dispersion medium. In order to increase the dispersibility of the raw material powder, a known dispersant such as ammonium polycarboxylate or calcium gluconate may be used. The mixed raw material slurry may be calcined as it is, or the raw material slurry may be dehydrated and then calcined.
[0058] The mixed raw material powder obtained by dry mixing or wet mixing is heated in a continuous or batch type electric furnace or gas furnace, etc., to form a ferrite compound with a hexagonal magnetoplumbite (M-type) structure through a solid-phase reaction. This process is called "calcination," and the resulting compound is called the "calcined body."
[0059] For example, when calcining is performed using a rotary kiln, which is a continuous gas furnace, if the calcining temperature is less than 1250°C, the amount of spinel ferrite phase formed in the calcined body is insufficient, resulting in poor magnetic properties. On the other hand, if the calcining temperature exceeds 1350°C, the spinel ferrite phase will be more than 30 mass%, resulting in poor magnetic properties. Therefore, the calcining temperature should be 1250°C or higher and 1350°C or lower. More preferably, it should be 1280°C or higher and 1330°C or lower, and even more preferably, it should be 1290°C or higher and 1320°C or lower.
[0060] In the pulverization step, the calcined body is pulverized (coarsely pulverized) using a hammer mill or the like, and then pulverized (finely pulverized) using a vibration mill, jet mill, ball mill, attritor, or the like to obtain pulverized powder. The average particle size of the pulverized powder is preferably about 0.4 μm to 1.2 μm. When emphasis is placed on improving the magnetic properties, the average particle size is preferably about 0.4 μm to 0.7 μm. When emphasis is placed on manufacturing costs (shortening the pulverization time, shortening the press cycle, etc.), the average particle size is preferably about 0.7 μm to 1.2 μm. In the present disclosure, the average particle size (average particle size) of the powder refers to a value measured by an air permeation method using a powder specific surface area measuring device (e.g., SS-100 manufactured by Shimadzu Corporation).
[0061] The pulverization step may be either dry pulverization or wet pulverization, or both may be combined. In the case of wet pulverization, water and / or a non-aqueous solvent (an organic solvent such as acetone, ethanol, or xylene) is used as a dispersion medium. Typically, a slurry containing water (dispersion medium) and the calcined body is produced. A known dispersant and / or surfactant may be added to the slurry in an amount of 0.2 to 2 mass% in terms of solid content. After wet pulverization, the slurry may be concentrated.
[0062] By going through the steps described above, the powder of the calcined ferrite body of the present disclosure can be obtained. Next, the method for producing the sintered ferrite magnet of the present disclosure will be described.
[0063] In the compacting step, the slurry after the pulverization step is press-molded in a magnetic field or without a magnetic field while removing the dispersion medium. By press-molding in a magnetic field, the crystal orientation of the powder particles can be aligned (oriented), and the magnetic properties can be improved dramatically. Furthermore, in order to improve the orientation, a dispersant and a lubricant may be added to the slurry before compacting in an amount of 0.1 to 1 mass % each. Furthermore, the slurry may be concentrated before compacting as necessary. Concentration is preferably performed by centrifugation, a filter press, or the like.
[0064] After the calcination step and before the molding step, a sintering aid is added to the calcined body or its pulverized powder. As the sintering aid, only SiO2, or both SiO2 and CaCO3, or Cr2O3 in addition to SiO2 and CaCO3 can be added. The amount of SiO2 added is preferably more than 0% by mass and 1.5% by mass or less with respect to 100% by mass of the calcined body or its pulverized powder to which it is to be added. When SiO2 is not added, H cJ The amount of SiO2 added is more preferably 0.4 to 0.7 mass %.
[0065] The amount of CaCO3 added is preferably more than 0 mass% and 1.5 mass% or less in terms of CaO relative to 100 mass% of the calcined body or its pulverized powder to which it is added. cJ The amount of CaCO3 added is more preferably 0.4 mass % or more and 0.0.6 mass % or less.
[0066] The amount of Cr2O3 added is preferably 2 mass% or less relative to 100 mass% of the calcined body or its pulverized powder to which it is added. If it is more than 2 mass%, B r The amount of Cr2O3 added is more preferably 1.5 mass % or less.
[0067] The sintering aid can be added, for example, by adding it to the calcined body obtained by the calcination step and then carrying out the pulverization step, by adding it during the pulverization step, or by adding it to the finely pulverized powder after the pulverization step and mixing it before carrying out the molding step, etc. In addition to SiO2, CaCO3, and Cr2O3, Al2O3, etc. may also be added as a sintering aid.
[0068] In this disclosure, the amount of CaCO3 added is expressed in terms of CaO. The amount of CaCO3 added can be calculated from the amount added in terms of CaO by the formula: (molecular weight of CaCO3 x amount added in terms of CaO) / molecular weight of CaO. For example, when 0.5% by mass of CaCO3 is added in terms of CaO, the amount is {(40.08[atomic weight of Ca]+12.01[atomic weight of C]+48.00[atomic weight of 0 x 3]=100.09[molecular weight of CaCO3]) x 0.5% by mass [amount added in terms of CaO]} / (40.08[atomic weight of Ca]+16.00[atomic weight of 0]=56.08[molecular weight of CaO])=0.892% by mass [amount added of CaCO3].
[0069] The compact obtained by press molding is degreased as necessary and then fired (sintered). Firing is performed using an electric furnace, a gas furnace, or the like. Firing is preferably performed in an atmosphere with an oxygen concentration of 10 volume % or more, more preferably 20 volume % or more, and most preferably 100 volume %. The firing temperature is preferably 1150°C to 1250°C. The firing time is preferably 0 hour (no holding at the firing temperature) to 2 hours.
[0070] During the temperature rise in the sintering process, the average temperature rise rate in the temperature range from room temperature to 1100°C is preferably 400°C / hour to 1000°C / hour, and the average temperature rise rate in the temperature range from 1100°C to the sintering temperature is preferably 1°C / minute to 10°C / minute. In addition, during the temperature drop after the sintering time is kept (including the case where the temperature is not held) in the sintering process, it is preferable to set the average temperature drop rate in the temperature range from the sintering temperature to 800°C to 300°C / hour or more, since this further improves the magnetic properties. Note that these effects can be obtained by adopting only the above-mentioned temperature drop rate, but it is more preferable to adopt both the above-mentioned temperature rise rate and temperature drop rate. In addition, all temperatures mentioned refer to the temperature of the heat-treated object. The temperature is measured by contacting an R thermocouple with the heat-treated object in the sintering furnace.
[0071] After the firing step, known manufacturing processes such as a machining step, a cleaning step, and an inspection step are performed, and finally, a sintered ferrite magnet is manufactured. EXAMPLES
[0072] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto.
[0073] Experimental Example 1 General formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3 CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed out in a predetermined composition, and 0.12 mass% of H3BO3 powder was added to the total of 100 mass% of the weighed powders, and then they were mixed in an attritor to obtain a mixed slurry. Note that Mn was contained in the Fe2O3 powder as an unavoidable impurity.
[0074] The resulting mixed slurry was calcined in air at the calcination temperatures shown in Table 1 to obtain eight types of calcined bodies. Samples No. 1 to No. 7 were calcined in a rotary kiln, and sample No. 8, which was a comparative example, was calcined in a box furnace (batch-type electric furnace). Each of the resulting calcined bodies was then coarsely pulverized in a small mill to obtain eight types of coarsely pulverized powders.
[0075] The phase ratios (mass%) of the constituent phases contained in the eight types of coarsely pulverized powders were determined. The results are shown in Table 1. The phase ratios were determined by performing X-ray diffraction using an X-ray diffractometer (D8 ADVANCE TXS manufactured by Bruker AXS) and subjecting the obtained X-ray diffraction patterns to Rietveld analysis.
[0076] CaCO3 (addition amount converted to CaO) and SiO2 shown in Table 1 were added to 100% by mass of eight kinds of coarsely ground powders, which were then finely ground in a wet ball mill using water as a dispersion medium to obtain finely ground slurries. The powders were finely ground until the average particle size (measured by air permeability method using a powder specific surface area measuring device (Shimadzu SS-100)) reached the particle size shown in Table 1.
[0077] While removing the dispersion medium, each finely pulverized slurry was molded using a parallel magnetic field molding machine (vertical magnetic field molding machine) in which the pressure direction and magnetic field direction are parallel, while applying a magnetic field of approximately 1 T and a pressure of approximately 2.4 MPa, obtaining eight types of molded bodies.
[0078] The obtained compacts were each placed in a sintering furnace, heated in air to 1100°C at a heating rate of 400°C / hour, heated from 1100°C to the firing temperature shown in Table 1 at a heating rate of 1°C / minute, fired for 1 hour, and cooled from the firing temperature shown in Table 1 to room temperature at an average cooling rate of 300°C / hour while supplying air at 10 L / minute, thereby obtaining eight types of sintered ferrite magnets. r , H cJ and H k / H cJ The measurement results are shown in Table 1. In Table 1, samples No. 1 to No. 7 without an * next to the sample No. are experimental examples based on the embodiment of the present disclosure, and sample No. 8 with an * is an experimental example (comparative example) that does not satisfy the embodiment of the present disclosure. k is in the second quadrant of the J (magnetization magnitude)-H (magnetic field strength) curve, where J is 0.95×J r (J r is the remanent magnetization, J r =B r ) is the value of H at the position where
[0079] [Table 1]
[0080] Comparing the magnetic properties of sample No. 8, which uses calcined powder containing 0 mass% spinel ferrite phase, with those of samples No. 1 to No. 7, which use calcined powder containing spinel ferrite phase, the B of samples No. 1 to No. 7 is r The characteristics are similar, and H cJ In all cases, high characteristics of 400 kA / m or more were obtained. Furthermore, when the spinel ferrite phase was 10 mass% or more and 20 mass% or less as shown in samples No. 2 to 6, H cJ The value was 420 kA / m or more, which is an extremely high characteristic.
[0081] Moreover, the results of Samples Nos. 1 to 7 show that the calcination temperature at which good magnetic properties can be obtained is 1250°C or higher and 1350°C or lower, and the results of Samples Nos. 2 to 6 show that the calcination temperature at which even better magnetic properties can be obtained is 1290°C or higher and 1320°C or lower.
[0082] Experimental Example 2 General formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3 CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed out in a predetermined composition, and 0.12 mass% of H3BO3 powder was added to the total of 100 mass% of the weighed powders, and then they were mixed in an attritor to obtain a mixed slurry. Note that Mn was contained in the Fe2O3 powder as an unavoidable impurity.
[0083] The resulting mixed slurry was calcined in the air using a rotary kiln at the calcination temperatures shown in Table 2 to obtain 10 types of calcined bodies. Each of the resulting calcined bodies was then coarsely pulverized in a small mill to obtain 10 types of coarsely pulverized powders.
[0084] The phase ratios (mass%) of the constituent phases contained in the 10 types of coarsely pulverized powders were determined and confirmed by the same method as in Experimental Example 1. It was confirmed that Samples Nos. 9 to 13, which were fired at a calcination temperature of 1,310°C, contained 12 mass% of the spinel ferrite phase, and Samples Nos. 14 to 18, which were fired at a calcination temperature of 1,330°C, contained 25 mass% of the spinel ferrite phase.
[0085] In order to investigate the composition ratio (at%) of each element when the total amount of each element (total amount of each element of Ca, La, Fe and Co) contained in the ferrite phase of the coarsely crushed powder of Samples No. 9 to 18 is taken as 100 at%, and the composition ratio (at%) of each element when the total amount of each element (total amount of each element of Ca, Fe, Co and Mn) contained in the spinel ferrite phase is taken as 100 at%, EDS (energy dispersive X-ray spectroscopy) analysis was performed using Fe-SEM (field emission scanning electron microscope) and the results are shown in Table 2.
[0086] [Table 2]
[0087] It was found that Mn was contained in the spinel ferrite phase and not in the ferrite phase in all of Samples No. 9 to 18. This suggests that forming a spinel ferrite phase in the calcined body has the effect of preventing Mn, which causes a decrease in magnetic properties, from being contained in the spinel ferrite phase and being contained in the ferrite phase, and as a result, a sintered ferrite magnet with excellent magnetic properties was obtained.
[0088] Experimental Example 3 General formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3 CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed out in a predetermined composition, and 0.12 mass% of H3BO3 powder was added to the total of 100 mass% of the weighed powders, and then they were mixed in an attritor to obtain a mixed slurry. Note that Mn was contained in the Fe2O3 powder as an unavoidable impurity.
[0089] The resulting mixed slurries were calcined in air at the calcination temperatures shown in Table 3 to obtain calcined bodies. All of the calcined bodies were calcined in a rotary kiln. Each of the resulting calcined bodies was then coarsely pulverized in a small mill to obtain coarsely pulverized powders.
[0090] The phase ratios (mass%) of the constituent phases contained in the coarsely pulverized powder were determined. The results are shown in Table 3. The phase ratios of the constituent phases were determined in the same manner as in Experimental Example 1.
[0091] CaCO3 (addition amount converted to CaO) and SiO2 shown in Table 3 were added to 100% by mass of the coarsely pulverized powder, and the powder was finely pulverized in a wet ball mill using water as a dispersion medium to obtain seven types of finely pulverized slurries. The powder was finely pulverized until the average particle size (measured in the same manner as in Experimental Example 1) reached the particle size shown in Table 3.
[0092] Each finely pulverized slurry was molded in the same manner as in Experimental Example 1 to obtain seven types of molded bodies.
[0093] The obtained compacts were each placed in a sintering furnace, heated in air to 1100°C at a heating rate of 400°C / hour, heated from 1100°C to the firing temperature shown in Table 3 at a heating rate of 1°C / minute, fired for 1 hour, and cooled from the firing temperature shown in Table 3 to room temperature at an average cooling rate of 300°C / hour while supplying air at 10 L / minute, thereby obtaining seven types of sintered ferrite magnets. r , H cJ and H k / H cJ The measurement results are shown in Table 3.
[0094] [Table 3]
[0095] From the results of samples No. 19 to No. 25, since the calcination temperature is within the range of 1290°C to 1320°C, the spinel ferrite phase is 10% by mass to 20% by mass, and H cJ The value was 420kA / m or more, which is an extremely high characteristic.
[0096] Experimental Example 4 General formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3 CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed out in a predetermined composition, and 0.12 mass% of H3BO3 powder was added to the total of 100 mass% of the weighed powders, and then they were mixed in an attritor to obtain a mixed raw material slurry. Note that Mn was contained in the Fe2O3 powder as an unavoidable impurity.
[0097] The resulting mixed raw material slurry was calcined in air at the calcination temperatures shown in Table 4 to obtain 18 types of calcined bodies. All of the calcined bodies were calcined in a rotary kiln. Each of the calcined bodies was then coarsely pulverized to obtain 18 types of coarsely pulverized powders.
[0098] The ratios (%) of the constituent phases contained in the 18 types of coarsely pulverized powders were determined. The results are shown in Table 4. The phase ratios were determined in the same manner as in Experimental Example 1.
[0099] CaCO3 (addition amount is CaO conversion), SiO2, and Cr2O3 shown in Table 3 were added to 100 mass% of 18 kinds of coarsely pulverized powders, and the powders were finely pulverized in a wet ball mill using water as a dispersion medium to obtain finely pulverized slurries. The powders were finely pulverized until the average particle size (measured in the same manner as in Experimental Example 1) reached the particle size shown in Table 4.
[0100] Each finely pulverized slurry was molded in the same manner as in Experimental Example 1 to obtain 18 types of molded bodies.
[0101] The obtained compacts were each placed in a sintering furnace, and heated in air to 1100°C at a heating rate of 400°C / hour, then heated from 1100°C to the firing temperature shown in Table 1 at a heating rate of 1°C / minute, and then fired for 1 hour. The temperature was then lowered from the firing temperature shown in Table 4 to 800°C at an average heating rate of 300°C / hour while supplying air at 10 L / minute, and then cooled to room temperature over 8.5 hours to obtain 18 types of sintered ferrite magnets. r , H cJ and H k / H cJ The measurement results are shown in Table 4.
[0102] [Table 4]
[0103] From the results of samples No. 26 to 43, it was found that adding Cr2O3 in addition to CaCO3 and SiO2 resulted in a higher H cJ In any case, the calcination temperature is within the range of 1290°C to 1320°C, so that the spinel ferrite phase is 10% by mass to 20% by mass, and H cJ The value was 420kA / m or more, which is an extremely high characteristic. [Industrial Applicability]
[0104] According to the present disclosure, it is possible to obtain a sintered ferrite magnet having excellent magnetic properties, and the provided sintered ferrite magnet can be suitably used in various motors and the like.
Claims
1. A compound having a general formula Ca1-x-yRxAyFe2n-zCoz showing the atomic ratio of metal elements Ca, R, A, Fe and Co (R is at least one rare earth element essentially including La, and A is Sr and / or Ba), wherein x, y, z and n (2n is a molar ratio expressed as 2n=(Fe+Co) / (Ca+R+A)) are: 0.30≦1−x−y≦0.65, 0.3≦x≦0.65, 0≦y≦0.2, 0.25≦z≦0.65, and 4.5≦n≦7 is satisfied, A ferrite calcined body containing more than 0 mass% and not more than 0.5 mass% Mn in terms of MnO, The magnetoplumbite-based alloy has a ferrite phase having a hexagonal M-type magnetoplumbite structure containing metal elements Ca, R, Fe and Co or metal elements Ca, R, A, Fe and Co, and a spinel ferrite phase containing Co, The ferrite phase contains 70% by mass or more and less than 100% by mass, and the spinel ferrite phase contains 10% by mass or more and 30% by mass or less, A ferrite calcined body, wherein the Mn content in the spinel ferrite phase is greater than the Mn content in the ferrite phase.
2. The ferrite calcined body according to claim 1, wherein 1-x-y satisfies the relationship 0.30≦1-x-y≦0.65 (excluding cases where the 1-x-y is less than 0.40).
3. The ferrite calcined body according to claim 1 or 2, further comprising more than 0 mass % and less than 3 mass % of a La orthoferrite phase.
4. The ferrite calcined body according to any one of claims 1 to 3, which is substantially free of a hematite phase.
5. The ferrite calcined body according to any one of claims 1 to 4, characterized in that the ferrite calcined body contains the spinel ferrite phase in an amount of 10 mass % or more and 20 mass % or less.
6. The ferrite calcined body according to any one of claims 1 to 5, wherein Mn is contained only in the spinel ferrite phase.
7. In the ferrite calcined body according to any one of claims 1 to 6, the spinel ferrite phase contains Ca, Fe, Co and Mn, and when the total amount of the elements is 100 at%, Ca: more than 0 at% and not more than 10 at%, Fe: 80 at% or more and 90 at% or less, Co: 2 at% or more and 15 at% or less, and Mn: more than 0 at% and not more than 5 at%, The calcined ferrite body is characterized in that the composition ratio is:
8. In the ferrite calcined body according to any one of claims 1 to 7, when the total amount of Ca, R, A, Fe and Co in the ferrite phase is taken as 100 at%, Ca: 2.0 at% or more and 6.5 at% or less, R: 2.0 at% or more and 6.5 at% or less, A: 0 at% or more and 2 at% or less, Fe: 83 at% or more and 92 at% or less, and Co: 1.5 at% or more and 6.5% or less, The calcined ferrite body is characterized in that the composition ratio is:
9. A method for producing a ferrite sintered magnet, comprising: a molding step of molding a pulverized powder of the ferrite calcined body calcined by the rotary kiln according to any one of claims 1 to 8 to obtain a molded body; and a sintering step of sintering the molded body to obtain a sintered body.
10. The method for producing a sintered ferrite magnet according to claim 9, The method for producing a sintered ferrite magnet is characterized in that the calcined body is calcined at a temperature of 1250°C or higher and 1350°C or lower.
11. The method for producing a sintered ferrite magnet according to claim 10, The method for producing a sintered ferrite magnet is characterized in that the calcined body is calcined at a temperature of 1280°C or higher and 1330°C or lower.
12. The method for producing a sintered ferrite magnet according to claim 11, The method for producing a sintered ferrite magnet is characterized in that the calcined body is calcined at a temperature of 1290°C or higher and 1320°C or lower.
13. The method for producing a sintered ferrite magnet according to any one of claims 9 to 12, The ferrite calcined body before the forming step has a SiO content of more than 0 mass % and not more than 1.5 mass % relative to 100 mass % of the ferrite calcined body. 2 4. A method for producing a sintered ferrite magnet, comprising the step of:
14. The method for producing a sintered ferrite magnet according to any one of claims 9 to 13, The ferrite calcined body before the forming step contains CaCO in an amount of more than 0 mass % and not more than 1.5 mass % in terms of CaO relative to 100 mass % of the ferrite calcined body. 3 4. A method for producing a sintered ferrite magnet, comprising the step of:
15. The method for producing a sintered ferrite magnet according to any one of claims 9 to 14, The ferrite calcined body before the forming step is added with 2 mass % or less of Cr relative to 100 mass % of the ferrite calcined body. 2 O 3 4. A method for producing a sintered ferrite magnet, comprising the step of:
Citation Information
Patent Citations
Permanent magnet and its manufacturing method
JP2002313618A
Method of manufacturing ferrite sintered magnet and ferrite sintered magnet
JP2008311535A
Method for manufacturing ferrite sintered magnet
JP2020155609A
Oxide magnetic material
WO2007077811A1
Sintered ferrite magnet, and process for production thereof
WO2011111756A1